Ottawa materials, Anthony F. C. Wallace Papers - Wallace, Anthony F. C., 1923-2015; Bauman, Robert F.; Kane, Michal Lowenfels; Stewart, Omer Call, 1908-1991 (1951)
The Anthony F. C. Wallace Papers are a vast collection of materials relating to Wallace's work at the intersection of anthropology, psychology, and history. Though further research might yield more results, approximately nine items directly pertaining to the Odawa (called Ottawa by Wallace) have been identified. Most of these materials are located in Series IX. Indian Claims, and relate to Wallace's work as a researcher and expert witness on behalf of Native American land claims. They include research notes, tribal histories, court dockets, trial memoranda, and a copy of Robert F. Bauman's "Ottawa, the Huron-Wyandot, and the Land" with several pages of handwritten notes [Robert F. Bauman was a lawyer and historian who specialized for a time as a research historian on Indian claims for a Cleveland law firm and was also briefly director of the Dearborn Historical Museum in the early 1950s.] See also the Omer Call Stewart file in Series I. Correspondence. See the finding aid for a detailed discussion of Wallace's long and varied career, and for an itemized list of the collection's contents.